Local Food-Based Supplementation and Behavior Change Communication Improve Mid-Upper Arm Circumference (MUAC) in Pregnant Women: A Community-Based Intervention Study - Dasmasela, Maya Klementina; Hardinsyah, Hardinsyah; Dewi, Mira; Ekayanti, Ikeu; Indrayana, Indrayana (Journal of Health and Nutrition Research, 2025)
Chronic Energy Deficiency (CED) in pregnant women remains a major nutritional issue in Indonesia and contributes to adverse birth outcomes and the risk of childhood stunting. Community-based interventions that integrate nutrition education and food supplementation have shown promise but remain underutilized. This study aimed to evaluate the effectiveness of an integrated nutrition intervention, consisting of Behavior Change Communication (BCC)-based education and local food-based supplementary feeding (PMT), on improving the Mid-Upper Arm Circumference (MUAC) and nutritional status of pregnant women in high-stunting prevalence areas. A 16-week quasi-experimental pre–post study was conducted among 175 pregnant women in Purbalingga, Serang, and Bogor, Indonesia. Participants received weekly group-based BCC education and daily local snack supplementation (≥350 kcal/day). MUAC, weight, BMI, hemoglobin levels, and dietary adequacy (energy, protein, fat, carbohydrate) were assessed pre- and post-intervention. Data were analyzed using the Wilcoxon Signed-Rank test and multiple linear regression. The mean MUAC increased significantly from 22.7 ± 1.1 cm to 23.6 ± 1.0 cm (p < 0.001), with a 27.4% reduction in CED prevalence. Regression analysis indicated that dietary compliance and baseline hemoglobin were strong predictors of MUAC improvement. The intervention also significantly increased maternal weight, BMI, and hemoglobin levels, while protein adequacy showed the most substantial improvement, aligning dietary intake more closely with national recommendations. The integration of BCC-based education with local PMT significantly improved maternal nutritional outcomes, particularly MUAC, protein adequacy, and hemoglobin status, thereby reducing the risk of CED and anemia. This dual-component approach is feasible for community-level stunting prevention and supports its inclusion in antenatal care services.